ECONOMIC FEASIBILITY ANALYSIS OF A PEANUT PROCESSING AGROINDUSTRY - Silva, Fernanda Eduarda Vieira da; Carvalho, Francislene de Fatima; Borges, Luana Coscolin; Claudino, Tainá da Silva; Pandolfi, Marcos Alberto Claudio (Revista Interface Tecnológica, 2020)
This article presents the importance of peanut cultivation for the growth of agribusiness in Brazil. Peanut is a legume originally from South America, and its fruit is rich in oil, proteins and vitamins. As it is a profitable activity for the local economy, a large part of peanut production has been destined for the fresh market, with boiled and roasted peanuts standing out. The state of São Paulo, Goiás, Mato Grosso and Paraná that stand out in the production for presenting the edaphoclimatic factors favorable to the culture. Peanut consumption, fresh or processed, indicates a growth trend in Brazil. The main challenges faced by the peanut culture are the high cost of labor, machinery that has high investment costs and often ends up interfering with the quality of the product. The economic indicators VPL, TIR, Playback were used to carry out the economic and financial analysis of the investment project for fresh peanut and peanut paste agroindustry in the city of Taquaritinga - SP. Therefore, the three applied methods (NPV most recommended method from an economic point of view, IRR, Internal Rate of Return on an investment, periodicity of the project's cash flows and Playback viability of an investment), are references for good management in search of profitability.